Climate change in Eastern Taimyr over the last 80 years and the warming impact on biodiversity and ecosystem processes in its territory - Pospelova, Elena B.; Pospelov, Igor N.; Orlov, Mikhail V. (Nature Conservation Research: Заповедная наука, 2017)
The analysis of long-term changes of mean annual temperatures and the active temperature sum over 80 years was carried out using data of the Khatanga meteorological station. Since the 1990s, an essential warming was observed, especially after 2000. The warming influence on vegetation takes place immediately (the ecosystem composition changes due to the degradation of cryogenic processes) as well as directly by increasing the time of the vegetation period and the total amount of heat on plants. As a result, in the last few years, the lead of phenological phenomena terms is observed – the time of foliage expansion and efflorescence of plants-indicators, geese arriving, mosquitos appearance, ice thawing. By long term monitoring data, the moving of some north-taiga plant species to forest tundra and tundra is observed, as well as their establishing in vegetation communities. However, at this moment, the character of the vegetation is stable. The occurrence of taiga animals is increased in tundra and forest tundra. An active revival of larch is observed in forest tundra and north sparse forests. A removing forest border to the north is not observed, but in the southern mountains of Taimyr its replacing on higher levels could be seen. A decreasing summer precipitation quantity increases the possibility of forest fires, spring and bog drying. It influences negatively on bog flora and near-water fauna. It is possible, that the main reason of the local climate change at the East of Taimyr is less connected to the global planet change, but much more to pulsations of the strong Siberian anticyclone.